AKURASI INFORMASI BIBEL DAN AL-QUR’AN TENTANG PERISTIWA MASA LALU DAN MASA DATANG - Hamam Thontowi (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Two major religions, Christianity and Islam, claim that their scriptures are God’s words and, therefore, divine, accurate, and without any mistakes. However, these statements are needed to be critically studied. This paper attempts to examine scriptural information on the events in the past and the future as presented by two holy books based on the true history or other signs. The author will discuss examples of events from the Bible and the Qur’an respectively. In the case of the Bible, the events include the floods in the age of prophet Nūh; Identity of Haman; The second coming of Jesus to the Earth before Paul; and The Kingdom of God. From the al-Qur’an, theauthor will present examples of the flood in the age of prophet Nūh; Identity of Haman; further information on Fir’aun; information on Rome after the defeat by the Persian Kingdom; and Cases of Abū Jahl and al-Walīd ibn Mughīrah. All those scriptural events will be examined comparatively in this paper.Keywords: al-Qur’an, Bibel, Informasi Skriptural, Peristiwa Masa Lalu dan Masa Kini